Eclampsia is still a nightmare for obstetrician-maternal and perinatal outcome in eclampsia patients at tertiary hospital and factors affecting the outcome - Kamble, Neha B.; Khandale, Surekha N.; Dahiwade, Shreya U. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Among the disorders that complicate pregnancy, pre-eclampsia and eclampsia are major causes of maternal and perinatal morbidity and mortality. Hypertensive disorders complicate 5% to 10% of all pregnancies and form a lethal trio with haemorrhage and infection. In India, the incidence of eclampsia ranges from 1 in 500 to 1 in 30 (0.5%-1.8%). Pre-eclampsia and eclampsia are a major cause of approximately 20% of all maternal deaths in USA and around half of them are associated with eclampsia. To study various factors associated with eclampsia and outcomes in eclampsia patients. Methods: It is a prospective observational study conducted in the department of obstetrics and gynaecology in a tertiary care hospital in Central India. The study was conducted for duration of two years from November 2019 to October 2021. Results: In our study we found that Maternal complications were present among 19.0% women with eclampsia. Among the patients with maternal complications, atonic PPH was present among 16.2% women, obstetric hysterectomy was required in 0.4%. Maternal mortality was present among 4.5% patients. Of maternal deaths, cerebrovascular accidents accounted for four maternal deaths followed by acute renal failure among three women. Pulmonary edema, HELLP syndrome and septicemia were the cause of maternal death among two, one and one women respectively. Among the newborns, 6.9% comprised of stillbirths and early neonatal death was observed among seven newborns 2.8%. Conclusions: Improving the antenatal care by proper antenatal visits, early booking, meticulous BP records at each antenatal visit and special attention to high-risk groups such as primigravida, teenage pregnancy and pregnancy-induced hypertension and early referral and specialist care is important for the improvement in the maternal and perinatal outcomes.